Bare-Root-Dip Treatment of Tomato Seedlings with Neem and Bacillus thuringiensis for the Management of Meloidogyne incognita (Indian Journal of Nematology, 2024)
A study was conducted to evaluate the nematicidal potential of neem and Bacillus thuringiensis in controlling M. incognita. 5% neem leaf extract (NLE) @ 10ml/seedling, 10% neem seed extract (NSE) @ 10ml/seedling, 1.1X 109 CFU/ml Bt formulations alone @ 10ml/seedling and neem+Bt in combination in the ratio1:1 and 2.5% carbofuran 3-G @ 10ml/seedling to control M. incognitainfesting tomato plants. Bare-root-dip treatment with NSE was effective and caused 97.3% and 120.3% significant increase (p